2010
DOI: 10.1158/0008-5472.can-09-4289
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cyclooxygenase-2 Inhibition Downregulates NF-κB, Resulting in Chronic Intestinal Inflammation in the Min/+ Mouse Model of Colon Tumorigenesis

Abstract: COX-2 inhibition prevents adenoma formation in humans and mouse models of colon cancer. The selective COX-2 inhibitor, celecoxib, reduces COX-2 and PGE2 expression and adenomas in the intestine of Min/+ mice after treatment for several weeks, but prolonged treatment increases PGE2 production, resulting in drug-resistant tumor formation and TGFβ-dependent intestinal fibrosis. In this study, we examined pathways that regulate COX-2 expression and suppress chronic intestinal inflammation. We show that NF-κB signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…As previously mentioned, the NF-B pathway plays a central role in inflammation (16,17). Persistent COX-2 inhibition through long-term treatment of celecoxib down-regulates NF-B activity in enterocytes (29). Therefore, COX-2 inhibition by J11-C1 in inflamed colon tissues may contribute to NF-B inhibition.…”
Section: Discussionmentioning
confidence: 94%
“…As previously mentioned, the NF-B pathway plays a central role in inflammation (16,17). Persistent COX-2 inhibition through long-term treatment of celecoxib down-regulates NF-B activity in enterocytes (29). Therefore, COX-2 inhibition by J11-C1 in inflamed colon tissues may contribute to NF-B inhibition.…”
Section: Discussionmentioning
confidence: 94%
“…Effectors of TLR4 activation are MyD88 and subsequently NFκB, which is a key signaling molecule for the inflammatory response and cytokine production (100, 106110). The LPS/TLR4/NFκB pathway has been suggested to be a target for colon cancer prevention because of the central role of NFκB in cell proliferation, transformation and tumor progression (107109). …”
Section: Obesity Increases Systemic Exposures To Intestinal Bacteriamentioning
confidence: 99%
“…As HO-1 defensive system, cyclooxygenase-2 (COX-2) production has also been upregulated by redox-sensitive transcription factors at the sites of inflammation [24]. It has been demonstrated that downregulation of COX-2 eventuates in reducing intestinal inflammation [25][26][27] and also leading to amelioration of the colitis [28,29]. In the present study, we aimed to evaluate the effects of nadroparin calcium, a LMWH, treatment on HO-1 expression, and redox-sensitive transcription factors levels (AP-1, NF-κB, and Nrf2), COX-2, TNF-alpha, and IL-6 in acetic acid (AA)-induced colitis in rats.…”
Section: Introductionmentioning
confidence: 99%